2009
DOI: 10.1085/jgp.200810109
|View full text |Cite
|
Sign up to set email alerts
|

Four Ca2+ Ions Activate TRPM2 Channels by Binding in Deep Crevices near the Pore but Intracellularly of the Gate

Abstract: TRPM2 is a tetrameric Ca2+-permeable channel involved in immunocyte respiratory burst and in postischaemic neuronal death. In whole cells, TRPM2 activity requires intracellular ADP ribose (ADPR) and intra- or extracellular Ca2+, but the mechanism and the binding sites for Ca2+ activation remain unknown. Here we study TRPM2 gating in inside-out patches while directly controlling intracellular ligand concentrations. Concentration jump experiments at various voltages and Ca2+ dependence of steady-state single-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
158
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(164 citation statements)
references
References 33 publications
6
158
0
Order By: Relevance
“…6G). In contrast, coactivating Ca 2+ ions were shown to remain at rapid equilibrium with the bulk cytosolic solution, even while a TRPM2 channel is open (10).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…6G). In contrast, coactivating Ca 2+ ions were shown to remain at rapid equilibrium with the bulk cytosolic solution, even while a TRPM2 channel is open (10).…”
Section: Discussionmentioning
confidence: 92%
“…The latter shows high (∼50%) sequence homology to the soluble mitochondrial enzyme NUDT9, an active ADP ribose (ADPR) pyrophosphatase (ADPRase) from the Nudix hydrolase family, which splits ADPR into AMP and ribose-5-phosphate (8). TRPM2 channels are coactivated by ADPR binding to NUDT9-H (9) and by Ca 2+ binding to unidentified intracellular binding sites (10). ADPR is the key that links TRPM2 activation to oxidative stress; in living cells exposed to ROS, ADPR is released from mitochondria (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The primary activators of TRPM2 are ADP-ribose (ADPR) and Ca 2ϩ (2)(3)(4); simultaneous binding of both agonists is required for channel opening (9). TRPM2 channels are homotetramers (10), and ADPR binds to the NUDT9-H domains located at the cytosolic C termini of the subunits, named based on sequence homology to the mitochondrial enzyme NUDT9 (2).…”
Section: Trpm2mentioning
confidence: 99%
“…[10][11][12][13] More recently, it has been reported that TRPM2 is activated by intracellular Ca 2+ . 14,15 TRPM4 is widely distributed and has some of the features of the Ca-NS of pancreatic cells, such as block by adenine nucleotides. 16 However, animals that carry a targeted deletion of TRPM4 do not have any defects in glucose tolerance or insulin secretion.…”
mentioning
confidence: 99%